(Im)Politeness in accepting compliments and making refusals through polite-nopoly game - Che Ismail, Nur Asyrani; Mohd Sukri, Hanna Insyirah; Mohd Sobri Paridaluddin, Noorfarida Filzah; Hashim, Haida Umiera; Aziz Hussin, Anealka (Universiti Teknologi MARA, Kedah, 2025)
Communication is one of the essential mediums of interaction towards fulfilling various communicative purposes such as requesting, asking, apologizing and many others. In communication, individuals demonstrate different communication styles of either with good manners, or commonly referred to as polite, or rather impolite. Previous research has utilised frameworks of politeness empirically but there is a lack of integration in terms of innovation to identify politeness among users. Thus, an innovation called Polite-Nopoly, a board game incorporating multiplayer-basis, turn-taking styles, and a scoreboard which assisted in identifying the types of politeness strategies and factors of using them based on several daily life situations is designed and developed. The development of the game is based on the ADDIE Model which comprises needs analysis, design and development process, implementation, then evaluation. The structure and concept of the game focuses on using language in response to compliments and refusals. The responses provided by the players are recorded in the scoreboard and further analysed based on Brown and Levinson’s (1987) Model of Politeness Theory. The findings showcase that the Polite-Nopoly game is compatible with being a platform in identifying politeness strategies used by the players which most players generally express positive politeness strategy through gratitude when receiving compliments and using negative politeness strategies by apologising mostly in making refusals. In addition to this, the choice of the politeness strategies is influenced by social distance and social power factors. Therefore, using the Polite-Nopoly game has the potential to be used by language users towards discovering their politeness style especially when entertaining compliments and refusals.